Temperature assessment in newborn: a better method - M. R., Prashanth; B. E., Pavithra Shree; K. B., Namratha (International Journal of Contemporary Pediatrics, 2023)
Background: Accurate temperature assessment is essential in neonatal care as minor temperature changes can have a significant impact on the health and well-being of newborns. The purpose of this study was to compare the performance of three different types of thermometers, including non-contact infrared, digital, and mercury thermometers, for temperature assessment in newborns. Methods: This was a prospective, comparative study conducted between April 2022 and August 2022 in Cheluvamba hospital, Mysuru. A total of 400 healthy newborns were included in the study. Temperature readings were taken from the mid-forehead non-contact infrared thermometer and axilla using digital and mercury thermometers, while maintaining aseptic precautions. Parental oral consent was obtained for participation. Results: The mean temperature recorded with the digital thermometer in the axilla was statistically higher than that recorded with the mercury thermometer. The non-contact infrared thermometer showed a strong positive correlation with the mercury thermometer for the axilla region. Conclusions: The digital thermometer is a useful device for easy and valid measurement of skin temperature in newborns, especially when applied to the axilla. The findings suggest that the use of digital thermometers for axillary temperature measurement in neonates is supported by previous studies, which have reported their accuracy and reliability in comparison to mercury thermometers. The non-contact infrared thermometer may have limitations and its accuracy may vary depending on the site of measurement. The use of digital thermometers for neonatal temperature measurement may be more convenient, less hazardous, and equally reliable compared to traditional mercury thermometers.